PERAN KEPUASAN NASABAH MEMEDIASI CORPORATE SOCIAL RESPONSIBILITY DENGAN LOYALITAS NASABAH (STUDI PADA NASABAH BANK BNI DI KOTA DENPASAR) - Lomi, Chyntia Maureen; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
This study was conducted to determine the role of customer satisfaction in mediating the effect of corporate social responsibility to the loyalty nasabahpada BNI bank customers in the city of Denpasar. The number of samples taken are as many as 100 respondents, using a non-probability sampling technique with purposive sampling method. Data collected through questionnaires. Data analysis techniques used in this research is the technique of path analysis (path analysis) which is an extension of the multiple linear regression analysis is useful for estimating the causal relationships between variables are then issued in the form of SPSS software for windows. These results indicate that customer satisfaction has a significant impact in mediating the effect of corporate social responsibility on customer loyalty in BNI bank in Denpasar. The implications of this study are advised to BNI bank in Denpasar in order to communicate the CSR activities that have been done in order to further increase customer satisfaction and customer loyalty increased
Keywords: corporate social responsibility; kepuasan nasabah; loyalitas nasabah